The Effect of the Working Environment on the Performance of the Development and Human Resources Development Agency of Lebong District (Studies in the State and Honorary Civil Apparatus) - Azis Fransutomo; Sulisti Afriani; Kaulan Kaulan (Jurnal Fokus Manajemen, 2021)
The purpose of this study was to determine the effect of the work environment on the performance of the State Civil Service and honorarium at the Human Resources Development and Human Resources Agency of Lebong Regency. The sample in this study were 62 employees at the Human Resources Development and Human Resources Agency of Lebong Regency. The sampling technique is a census. Collecting data using a questionnaire and the method of analysis used is simple linear regression, test of determination and hypothesis testing. The results showed the regression value Y = 16.519+ 0.590X with a positive regression direction, meaning that if the work environment increases, the performance of employees at the Human Resources and Development Agency for Lebong Regency will also increase. The work environment has a significant effect on the performance of employees at the Human Resources and Development Personnel Agency of Lebong Regency, because the significant value is 0.000, which is smaller than 0.05. This means that the increasing work environment for employees of the Human Resources and Development Personnel Agency of Lebong Regency, the performance will also increase. This illustrates that with self-control from employees, employee performance will increase. The coefficient of determination of the R square is 0.345. This means that the work environment and professionalism have an effect on performance by 34.5%, while the rest (100-34.5% = 65.5%) are influenced by other causal factors which were not examined in this study.